Ferramenta computacional direcionada à análise de antenas impressas por meio da utilização do método de FDTD em paralelo desenvolvida em CUDA - Ravel Carlos de Miranda Pimenta (2018)
In the present project, a computational application is developed to analyze generic electromagnetic devices, using a paralell algorithm of the FDTD method terminated by Convolutional Perfectly Matched Layer (CPML) Absorbing Boundary Conditions. Despite of its versatility, this project is focused on the use of the application developed to analyze microstrip antennas. The CUDA computing platform is used to develop the program, therefore, are view of it simple mentation characteristics is performed. The Unied Memory component, provided by CUDA, is used to accomplish the encapsulation of the program, as well as the memory access management. CUDA optimzation strategies are used to explore the developed program to its maximum. Performance characteristics are analyzed and simulations performed to validate the program. The impact on performance due the use of CPML, instead of the Perfect Electric Conductor (PEC) Boundary Contition, is also analyzed.